Factors Influencing Consumer Adoption of Mobile Payment Systems in Jambi, Indonesia: A Technology Acceptance Model Approach - Delvita Juniarsih; Panji Ulum; Darmawanto; Eva Marlina; Hamirul; Feri Antoni (Enigma Institute, 2024)
Mobile payment systems (MPS) are rapidly transforming financial transactions in Indonesia, including in Jambi Province. However, the adoption rate varies significantly. This study investigates the factors influencing consumer adoption of MPS in Jambi, Indonesia, using the Technology Acceptance Model (TAM) as a theoretical framework. A quantitative approach was employed, involving a survey of 300 consumers in Jambi Province. Data were analyzed using Structural Equation Modeling (SEM) to examine the relationships between perceived usefulness, perceived ease of use, social influence, trust, perceived risk, and the intention to use MPS. The findings revealed that perceived usefulness, perceived ease of use, social influence, and trust positively influence the intention to use MPS. Conversely, perceived risk negatively affects adoption intention. This study provides valuable insights for policymakers, financial institutions, and mobile payment providers to promote MPS adoption in Jambi. Strategies should focus on enhancing the perceived usefulness and ease of use of MPS, building trust, leveraging social influence, and mitigating perceived risks.